Enantioselective synthesis of HIV protease inhibitor amprenavir via Co-catalyzed HKR of 2-(1-azido-2-phenylethyl)oxirane - Gadakh, Sunita K.; Reddy, R. Santhosh; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A short and efficient enantioselective synthesis of the HIV protease inhibitor amprenavir 1 (99% ee) as well as a formal synthesis of saquinavir 3 have been achieved in high enantiomeric purity starting from commercially available materials. Our strategy mainly comprises a Co-catalyzed two-stereocentred hydrolytic kinetic resolution (HKR) of racemic 2-(1-azido-2-phenylethyl)oxirane as the chirality inducing step. Also presented is a concise synthesis of (S)-3-hydroxytetrahydrofuran 4, the key structural feature, in high enantiomeric purity (98% ee). (c) 2012 Elsevier Ltd. All rights reserved.

Simple and efficient synthesis of isocoumarins and alkylidenephthalides from 3-(1-hydroxycarbethoxy/alkyl)phthalides with a DEAD/PPh3/TBHP system - Gadakh, Sunita K.; Sudalai, Arumugam (RSC Advances, 2014)
A facile and novel approach to the synthesis of 3-carbethoxy-isocoumarins and 3-alkylidenephthalides is described. The methodology employs DEAD/PPh3/TBHP as the reagent system proceeding through unprecedented 1,2-shift intramolecular ring expansion or simple elimination depending upon substituents present on 3-substituted phthalides, with broader substrate scope. This strategy is amply demonstrated in the short synthesis of bioactive molecules such as cytogenin and (Z)-3-butylidene-7-hydroxy-5-methoxyphthalide.

Co-catalyzed two-stereocentered hydrolytic kinetic resolution: application to the synthesis of yashabushidiols A and B and the lactone unit of compactin and mevinolin - Gadakh, Sunita K.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A short and efficient enantioselective synthesis of yashabushidiols A and B and the beta-hydroxy-delta-lactone moiety of compactin and mevinolin with high enantiomeric purity (98% ee) is described starting from commercially available materials. The strategy mainly comprises of iodine-induced intramolecular electrophilic addition of a carbonate occurring in a highly diastereoselective fashion and the Co-catalyzed two-stereocentered hydrolytic kinetic resolution of a functionalized epoxide as the chiral inducing step. (C) 2014 Elsevier Ltd. All rights reserved.

Rh-catalyzed synthesis of coumarin derivatives from phenolic acetates and acrylates via C-H bond activation - Gadakh, Sunita K.; Dey, Soumen; Sudalai, Arumugarn (Journal of Organic Chemistry, 2015)
An efficient annulation strategy involving the reaction of phenolic acetates with acrylates in the presence of [Rh-2(OAc)(4)] as catalyst and formic acid as reducing agent, leading to the high yield synthesis of coumarin derivatives, has been developed. The addition of NaOAc as a base increased the yield of the products. The reaction is quite Successful for both electron rich as well as electron deficient phenolic acetates, affording coumarins with excellent regioselectivity, and proceeds via, C-H bond activation proven by deuterium incorporation studies.

Titanium superoxide - a stable recyclable heterogeneous catalyst for oxidative esterification of aldehydes with alkylarenes or alcohols using TBHP as an oxidant - Dey, Soumen; Gadakh, Sunita K.; Sudalai, A. (Organic & Biomolecular Chemistry, 2015)
Titanium superoxide efficiently catalysed the oxidative esterification of aldehydes with alkylarenes or alcohols, under truly heterogeneous conditions, to afford the corresponding benzyl and alkyl esters in excellent yields. Mechanistic studies have established that this ``one pot'' direct oxidative esterification process proceeds through a radical pathway, proven by a FTIR spectral study of a titanium superoxide-aldehyde complex as well as spin trapping experiments with TEMPO. The intramolecular version of this protocol has been successfully demonstrated in the concise synthesis of 3-butylphthalide, an anti-convulsant drug.

Formal total synthesis of anti-helicobacter pylori agent (+)-spirolaxine methyl ether - Gadakh, Sunita K.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A convergent, formal enantioselective synthesis of anti-Helicobacter pylori agent, (+)-spirolaxine methyl ether 2 has been achieved in high enantiomeric purity starting from commercially available 1,5-pentanediol. The strategy mainly comprises of the Noyori's asymmetric reduction and Brown allylation/Cu-catalyzed lactonization as the key step for the construction of key chiral intermediates, spiroketal 3 and phthalide fragment 4. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Brown allylation; Cu-catalyzed lactonization; Noyori's asymmetric reduction; Phthalide; Spiroketal

Pd-catalyzed reductive cleavage of N-N bond in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates with PMHS: application to a formal enantioselective synthesis of (R)-sitagliptin - Dey, Soumen; Gadakh, Sunita K.; Ahuja, Brij Bhushan; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
An environmentally benign approach involving Pd-catalyzed reductive N-N bond cleavage in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates leading to the synthesis of N-(tert-butoxy)carbamates under very mild conditions has been described. PMHS serves as an inexpensive source of hydride in MeOH/deionized H2O medium. This protocol has been successfully applied in the formal synthesis of (R)-sitagliptin, an anti-diabetic drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: anti-Diabetic; Environmentally benign; Hydrazine; PMHS; Reductive cleavage

Rhodium-catalyzed ortho C-H bond activation of arylamines for the synthesis of quinoline carboxylates - Gadakh, Sunita K.; Dey, Soumen; Sudalai, A. (Organic & Biomolecular Chemistry, 2016)
The rhodium catalyzed annulation of anilines with alkynic esters allowing for the high-yield synthesis of quinoline carboxylates with excellent regioselectivity is described. This unprecedented reaction employs either formic acid as the C1 source and reductant or copper(II) as the oxidant and is proposed to proceed via rhodacycle of in situ generated amide and enamine ester followed by ortho C-H activation of arylamines with rhodium as the catalyst.